On Possibility Meanings of 'Could' in Written English - Huschová Petra (Univerzita Tomáše Bati ve Zlíně, 2015)
This paper is concerned with possibility meanings of the modal auxiliary 'could', focusing primarily on interpreting its contextualized occurrences in contemporary written British English. Although 'could' conveys essentially root possibility and is commonly employed as the preterite form of 'can' in past contexts, this paper explores its occurrence in non-past contexts and its potential epistemic interpretations. In order to obtain a complex picture of the usage and distribution of 'could' conveying possibility, discourse and stylistic aspects are included as well. The former relates to the usage of the modal verb as a hedging device, whereas the latter is reflected in the selection of the excerpted material; the data have been drawn from administrative, academic, popular scientific and journalistic texts.
Možnostní významy modálního slovesa 'could' v psané angličtině
Keywords: the modal verb 'could'; epistemic possibility; root possibility; gradience; hedging; modální sloveso 'could'; epistemická možnost; dispoziční možnost; gradience; atenuace